Chapter Lo slavo tra iranico ed Europa - Enrietti, Mario (Biblioteca di Studi Slavistici, 2019)
This article treats the glottogenesis or emergence of Slavic and examines different theories regarding the nature of influences on the Slavic language first from Iranic and subsequently from Proto-Romanian. We also consider the thesis that Slavic represents a further evolution of Baltic.